Synthesis, crystal structures and vapor adsorption properties of mercury(II) coordination polymers derived from two dipyridylamide ligands. Issue 6 (1st February 2021) - Chen, Ya‐Ting; Ding, Yan; He, Shan‐Xian; Huang, Chao; Chen, Dong‐Mei; Zhu, Bi‐Xue
Abstract: Two complexes, [HgL 1 Cl2 ] n (1 ) and [Hg2 (L 2 )2 Cl4 ] n (2 ), have been synthesized and characterized from two dipyridylamide ligands (L 1 and L 2 ) with mercury(II) chloride, respectively. The two complexes exist as 1D coordination polymers but exhibit different architectures with slightly adjusted 3‐ and 4‐position of nitrogen atom in the pyridyl rings from the two ligands. In complex 1, the mercury(II) center is four‐coordinated with distorted tetrahedral geometry in 1D‐chain structures. In complex 2, the mercury(II) center is five‐coordinated with distorted square pyramidal geometry in the 1D‐looped structures. The thermal stabilities and vapor adsorption properties of the two complexes were investigated as well. Abstract :